Frozen shoulder or missed posterior dislocation? - Leijnen, D (South African Journal of Sports Medicine, 2015)
The clinical presentation of a missed posterior shoulder dislocation has similarities with an idiopathic frozen shoulder masking proper diagnosis at the time of injury. We report a case of a 48-year-old woman with shoulder pain which demonstrates the importance of correct initial diagnosis and management.